Technology of formation of physical activity in children of preschool age - Jumayeva Sanobar Absaatovna PhD,; Rasulova Fayyoza Abdusalomovna (Periodica Journal, 2022)
The first step is to consider the state curriculum of the preschool organization, the importance of physical education in preschool children, the development of physical qualities, goals, objectives, role, requirements for the physical development of preschool children.
Keywords: The first step is the requirements of the state curriculum, the importance of physical education; physical qualities; goals; objectives